An evaluation of the infection agents and the demographic characteristics of patients followed up on a mechanical ventilator in neurology intensive care: A retrospective, single center, observational study - İnanç, Yılmaz and İnanç, Yusuf (Journal of Surgery and Medicine, 2018)
Aim: The incidence of nosocomial infections is higher than other sites of the hospitals at intensive care units (ICU) because of high frequency of invasive interventions and multidrug resistant microorganism’s prevalence. Ventilator-related pneumonia cases have the highest mortality risk among the nosocomial infections. The aim of this study was to evaluate the endotracheal aspirate cultures and the demographic characteristics of patients followed up on mechanical ventilation in Neurology Intensive Care. Methods: Our study was designed as a retrospective, cross-sectional and descriptive. Retrospective evaluation was made of 51 patients who were attached to a mechanical ventilator in the last 6 months and from whom a tracheal aspirate culture was taken. The endotracheal aspirate samples were taken under sterile conditions using a specifically designed catheter with the method of administering saline into the intubation tube and then aspiration. Blood culture results sent for analysis at the same time as the tracheal aspirate samples were also retrospectively evaluated in patients determined with positive production. A record was made of the demographic characteristics of the patients, diagnosis on admittance to ICU, risk factors, and microbial production in the tracheal aspirate culture. Results: In the first culture, there was no production in 22 (43.1%) cases, and Acinetobacter baumanii was determined in 14 (27.5%) patients, Pseudomonas aeruginosa in 3 (5.9%), Klebsiella pneumonia in 3 (5.9%), Staphylococcus aureus in 2 (3.9%), Corynebacterium striatum in 2 (3.9%), Acinetobacter baumanii + Pseudomonas aeruginosa in 2 (3.9%), Acinetobacter baumanii + Klebsiella pneumonia in 2 (3.9%), and Acinetobacter baumanii + Escherichia coli in 1 (2.0%). The second culture was taken from patients on the mean 11th day. In 3 (10.7%) patients there was no production in the second culture and in the other patients, Acinetobacter baumanii was determined in 15 (53.6%) patients, Pseudomonas aeruginosa in 3 (10.7%), Klebsiella pneumonia in 2 (7.1%), Escherichia coli in 1 (3.6%), Corynebacterium striatum in 1 (3.6%), and Acinetobacter baumanii + Pseudomonas aeruginosa in 3 (10.7%). Conclusion: The culture results in this study of patients admitted for neurological reasons were observed to be consistent with findings in literature. The high mortality rate of 64.7% in these ICU patients is due to the majority being ischemic stroke patients. This suggests that both the severe table associated with neurological findings and agents such as Acinetobacter baumanii and Pseudomonas aeruginosa contribute to Neurology ICU patients.